2003
DOI: 10.1051/0004-6361:20030323
|View full text |Cite
|
Sign up to set email alerts
|

Limits on diffusive shock acceleration in supernova remnants in the presence of cosmic-ray streaming instability and wave dissipation

Abstract: Abstract. The instability in the cosmic-ray precursor of a supernova shock moving in interstellar medium is studied. The level of magnetohydrodynamic turbulence in this region determines the maximum energy of particles accelerated by the diffusive shock acceleration mechanism. A high efficiency of cosmic ray acceleration is accepted, and the consideration is not limited by the case of weak turbulence. It is assumed that Kolmogorov-type nonlinear wave interactions together with the ion-neutral collisions restri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
164
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(173 citation statements)
references
References 45 publications
4
164
0
Order By: Relevance
“…The maximum energy of the particles accelerated in supernova remnants in the presence of large acceleration efficiencies was also studied in [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The maximum energy of the particles accelerated in supernova remnants in the presence of large acceleration efficiencies was also studied in [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…This motivates us to measure any possible time variation of the gammaray spectrum over long timescales. It has been shown that the maximum energy of CRs confined in SNRs depends on the SNR age during the Sedov phase (e.g., Ptuskin & Zirakashvili 2003;Ohira et al 2012). Since the downstream magnetic field strength around the shock decays with the shock velocity, as the SNR ages it becomes harder to confine high-energy CRs through pitch-angle scatterings near the shock.…”
Section: Ess (Actismentioning
confidence: 99%
“…The value of α is important for understanding the average source spectrum of Galactic CRs, which should be steeper than E −2 ). Although there are theoretical studies on α (e.g., Ptuskin & Zirakashvili 2003;Yan et al 2012), its precise value has not yet been determined observationally or theoretically. To reproduce the spectrum of Galactic CRs, we can phenomenologically assume that E max,p ≈10 15.5 eV at the beginning of the Sedov phase (t Sedov ), and that E max,p ≈1 GeV at the end of the Sedov phase (≈10 2.5 t Sedov ), from which we can obtain α≈2.6 ).…”
Section: Ess (Actismentioning
confidence: 99%
“…Ptuskin & Zirakashvili 2003): Γw = ΓL + ΓNL. The first one is due to collisions of protons with neutral hydrogen of the density nH (e.g.…”
Section: Equation For the Downstream Evolution Of δBmentioning
confidence: 99%
“…There is no commonly accepted approach to the description of the non-linear damping (see e.g. Ptuskin & Zirakashvili 2003, and references therein). We take the expression for the rate of non-linear Landau damping from Ptuskin & Zirakashvili (2003), namely from their Eq.…”
Section: Equation For the Downstream Evolution Of δBmentioning
confidence: 99%